Factors Contributing to Catch-Up Growth of Child with Stunting: A Literature Review - Ayuni Rizka Utami; Nani Nurhaeni (Universitas STRADA Indonesia, 2021)
Stunting is the main problems for children in Indonesia, children who are already stunted can catch-up growth to minimize the impact of stunting. This literature study aims to identified the factors contribute to catch-up growth in children with stunting. Literature search several online databases with the keyword